Initial evidence for the assimilation hypothesis. Issue 10 (26th November 2017) - Rassin, Eric
ABSTRACT: The assimilation hypothesis dictates that knowledge of prior evidence makes legal decision makers assign more weight to subsequent evidence. For example, the evidentiary power of a line-up identification is perceived to be stronger if the decision maker knows that the suspect has confessed, compared to when knowledge of the confession is absent. In three studies, the assimilation hypothesis was tested. As expected, knowledge of DNA-evidence inflated the estimated strength of subsequent eyewitness identification evidence (Study 1), and also inflated overall conviction and conviction rate (Study 2). A similar assimilation effect was found with knowledge of the suspect's dangerous psychopathology (i.e. psychopathic and anti-social personality traits). Such knowledge inflated the estimated strength of fingerprint evidence. In conclusion, the assimilation effect is a threat to rational legal decision making in both lays (Study 2) and professional judges (Studies 1 and 3).